Efektivitas Chatbot-AI dalam Pembelajaran Matematika melalui Model NHT berbasis PBL di SMPN 3 Binamu - Husriani Husain; Syaharuddin Syaharuddin; Yasriuddin Yasriuddin; Sri Wahyuni Agustina (Mandalika Mathematics and Educations Journal, 2026)
Mathematics learning in the digital era requires instructional strategies that enhance conceptual understanding while fostering students’ motivation and engagement. Integrating artificial intelligence into classroom practice offers a promising solution to these challenges. This study aimed to examine the effectiveness of integrating an AI chatbot into the Numbered Heads Together (NHT) model based on Problem-Based Learning (PBL) in improving students’ mathematical conceptual understanding and learning motivation. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The sample consisted of two eighth-grade classes at SMPN 3 Binamu, each comprising 30 students. The experimental group received NHT-based PBL integrated with an AI chatbot, whereas the control group received NHT-based PBL without chatbot support. Data were collected through a conceptual understanding test, a learning motivation questionnaire, and an observation sheet, and were analyzed using independent samples t-test, paired samples t-test, N-Gain, and Cohen’s d. The results revealed a significant difference in learning outcomes between the two groups (p < 0.05). The N-Gain and effect size were moderate, students’ motivation was high, and engagement was very good. These findings indicate that integrating an AI chatbot into NHT-based PBL effectively enhances mathematics learning quality.